2008
DOI: 10.1002/mmnz.20010770208
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary aspects of dietary selection and digestion in the European roe deer (Capreolus capreolus) with special reference to seasonality

Abstract: The European roe deer (Cupreolus cupreolus) is the smallest wild ruminant species in the northern hemisphere. Capreolini are represented in the fossil record of Eurasia by an array of forms extending from the Miocene to the Recent. Interestingly, a map of fossil occurrences shows that the historical range is fairly congruent with the recent distribution of Capreolirs; roe deer have always been temperate-zone animals of Eurasia (Lister et al. 1998). In contrast to many other large herbivores the roe deer popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Despite the widely accepted assumption that Procapreolus cusanus is closely related to or even a direct ancestor of Capreolus, the origin of Capreolus within Procapreolus is still under debate (Lechner-Doll et al, 2001). Some authors hypothesise that it may be assigned to Capreolus rather than Procapreolus (Valli, 2010).…”
Section: Procapreolus Cusanusmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the widely accepted assumption that Procapreolus cusanus is closely related to or even a direct ancestor of Capreolus, the origin of Capreolus within Procapreolus is still under debate (Lechner-Doll et al, 2001). Some authors hypothesise that it may be assigned to Capreolus rather than Procapreolus (Valli, 2010).…”
Section: Procapreolus Cusanusmentioning
confidence: 99%
“…Some authors hypothesise that it may be assigned to Capreolus rather than Procapreolus (Valli, 2010). Others place it in an intermediate position between lower Pliocene and Pleistocene Procapreolus species and extant Capreolus (Czyżewska, 1968;Heintz, 1970;Lechner-Doll et al, 2001).…”
Section: Procapreolus Cusanusmentioning
confidence: 99%
“…In the lowland habitat studied, deer also favoured monocotyledonous crops, as a relatively high proportion of these samples contained autumn-sown cereals, which are a very important food for roe deer during the autumn-winter period, similar to the results of Mátrai (2000), where his findings showed that roe deer dietary choice in the field habitat differed only in the crops consumed and not in their distribution. Roe deer have been classified as a typical concentrate selector, browsing on highly digestible plant parts (Lechner-Doll et al, 2008).…”
Section: Discussionmentioning
confidence: 99%